Super-hydrophobic PVC (polyvinyl chloride) material, preparation method and PVC drain pipe
By using modification additives in PVC materials, the combination of inorganic hard particles and anti-adhesion layer is used to form nano-scale bumps, which solves the problem of hair accumulation in PVC materials in high humidity environments and achieves the efficient hydrophobicity of the material and improve mechanical properties.
Patent Information
- Application Number
- CN202411608747.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
AI Technical Summary
PVC materials are prone to hair accumulation in high humidity environments, resulting in clogging of pipes. Existing solutions such as mechanical occlusion cleaners and chemical dredging agents cannot eliminate hair adsorption from the root and are costly and unsustainable.
Using a superhydrophobic PVC material, by adding a modification additive to the PVC resin, the additive is cored from inorganic hard particles, and the surface is covered with continuous anti-adhesion layer and uncovered anti-adhesion layer, and fluorine-containing The organic silicone cross-linked cured substance and titanate coupling agent form nanoscale bumps, improving the hydrophobicity of the material to reduce hair accumulation.
It significantly improves the hydrophobicity of PVC materials, reduces the accumulation of hair on the inner wall of the tube, reduces the infiltration of water, improves the convenience of hair removal, and maintains the mechanical properties of the material, avoids the agglomeration phenomenon, and enhances the Overall properties of the material.
Smart Images

Figure BDA0005130371570000091 
Figure BDA0005130371570000101
Abstract
Description
Technical Field
[0001] The present application relates to a drainage pipeline, and in particular to a super-hydrophobic PVC material, a preparation method and a PVC drainage pipe. Background Art
[0002] As an indispensable part of modern buildings, the performance of drainage systems directly affects the quality of life of residents. In recent years, with the acceleration of urbanization, the demand for efficient drainage systems has been growing. PVC materials, with their excellent chemical stability, light weight, durability and low cost, have been widely used around the world, especially playing a key role in the drainage networks of civil and commercial buildings.
[0003] However, despite its excellent performance, PVC still faces a common challenge: pipe clogging caused by hair accumulation, especially in high-humidity environments such as bathrooms and dressing rooms. This problem not only troubles ordinary families, but also brings a heavy burden to managers of public facilities.
[0004] To deal with this stubborn problem, the industry has tried a variety of methods, such as mechanical plug removers and chemical unclogging agents. Although these measures can achieve certain results in the short term, they are not sustainable solutions in the long run due to the need for frequent operations and high operating costs. More importantly, they do not eliminate the possibility of hair adsorption from the root, but are only a temporary solution. Summary of the invention
[0005] In order to reduce the accumulation of hair on the inner wall of a PVC pipe, a super-hydrophobic PVC material, a preparation method and a PVC drainage pipe are provided.
[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A super-hydrophobic PVC material comprises the following raw materials in parts by weight: 100 parts of PVC resin, TPE 1 to 3 parts, 1.5-2 parts of titanium dioxide, CR 1 to 3 copies, Modification additive 5-12 parts, The particle size of the modified auxiliary agent is 300 to 400 nm. The modification auxiliary agent has inorganic hard particles as the core, and comprises a continuous anti-sticking layer and a bonding surface not covered with anti-sticking. The anti-sticking layer is formed by curing fluorine-containing organic siloxane.
[0007] By adopting the above technical solution, the fluorinated organosiloxane cross-linked cured product has excellent hydrophobic properties, but the fluorinated organosiloxane cross-linked cured product microspheres are poorly dispersed in the PVC resin and are easy to agglomerate. Even with other compatibilizers to assist in dispersion, a large amount of fluorinated organosiloxane cross-linked cured product microspheres must be added to make the surface of the PVC material have considerable hydrophobicity. In addition, the mechanical strength of the fluorinated organosiloxane cross-linked cured product microspheres is lower than that of PVC. Excessive addition of fluorinated organosiloxane cross-linked cured product microspheres will lead to a decrease in the mechanical properties of the PVC material. The modified additive in the present application has an inorganic hard particle as the core, and its surface has both a continuous anti-sticking layer and a bonding surface that is not covered with anti-sticking. The compatibility of the bonding surface with the PVC resin is better than that of the anti-sticking layer with the PVC resin. Due to the existence of the bonding surface, the modified additive can be evenly dispersed into the PVC resin under shear force when the PVC resin is melted, thereby avoiding the agglomeration of the modified additive. Then, due to the existence of the anti-adhesive layer, the dispersion of the modifying agent in the PVC resin is not completely homogeneous. The distribution density of the modifying agent on the surface of the PVC material is greater than that inside the PVC material. In addition, due to the compatibility of the anti-adhesive layer and the tension of the PVC resin when it is melted, the modifying agent also forms nano-scale convex points when it is dispersed on the surface of the PVC material. Therefore, the PVC material of the present application can add less fluorine-containing organosiloxane cross-linked solidified material, while maintaining the strength performance of the PVC material up to standard, and hydrophobic modification is performed on the surface of the PVC material to form a large number of hydrophobic nano-protrusions, which significantly improves the hydrophobicity of the surface of the PVC material, reduces the infiltration of water on the surface of the PVC material, and makes it easier to wash away hair, thereby reducing the accumulation of hair on the inner wall of the PVC tube made of PVC material.
[0008] Optionally: The preparation method of the modification aid is as follows: Inorganic hard particles of 0.6 to 2 μm are added to a mixed solution for reaction, filtered and dried after the reaction to obtain modified inorganic hard particles, the modified inorganic hard particles are ball-milled to obtain slurry, the slurry is filtered, dried and sieved to obtain a modified auxiliary agent; the mixed solution includes water and tridecafluorooctyltrimethoxysilane.
[0009] By adopting the above technical solution, the anti-sticking layer is first wrapped on the surface of the inorganic hard particles, and then the particles are crushed by ball milling to obtain a new surface, thereby effectively controlling the continuity and coverage area of the anti-sticking layer, and the preparation of the modified additive is more convenient.
[0010] Optionally: The preparation method of the modification aid is as follows: Inorganic hard particles of 7 to 9 μm are added to the mixed solution for reaction, filtered and dried after the reaction to obtain first-level modified particles, the first-level modified particles are ball-milled to obtain first-level slurry, the first-level slurry is filtered, dried and sieved to obtain intermediate particles; the intermediate particles are added to another mixed solution for reaction, filtered and dried after the reaction to obtain second-level modified particles; The secondary modified particles are crushed by ball milling to obtain secondary slurry, and the secondary slurry is filtered, and the filtered material is dried and sieved to obtain composite modified particles; the mixed liquid includes water and tridecafluorooctyltrimethoxysilane.
[0011] By adopting the above technical scheme, the surface of the inorganic hard particles is covered with a fluorine-containing organosiloxane cross-linked solidified material, crushed, then covered with a fluorine-containing organosiloxane cross-linked solidified material, and then crushed again, the coverage density of the anti-sticking layer on the modified auxiliary agent particles can be gradually increased or decreased, and a "pole" is formed in the area with the maximum coverage density of the anti-sticking layer. The compatibility between the pole and the PVC resin on the anti-sticking layer is relatively the worst, and the compatibility between the anti-sticking layer far away from the "pole" and the PVC resin is relatively good, so that the modified auxiliary agent is easier to migrate and disperse to the surface of the PVC material, and it is easier to form nano-scale protrusions outward from the "pole", and the resulting PVC material has better hydrophobicity.
[0012] Optionally, the composite modified particles are further modified by soaking in a titanate coupling agent solution.
[0013] By adopting the above technical scheme, the compatibility of the titanate coupling agent with the fluorinated organosiloxane cross-linked solidified product is relatively weak. The titanate coupling agent can effectively modify the surface newly formed by the crushing of the composite modified particles, enhance the compatibility of the bonding surface with the PVC resin, and reduce the possibility of agglomeration of the modified additives caused by multiple coverings of the fluorinated organosiloxane cross-linked solidified product. On the other hand, another "pole" with good compatibility with the PVC resin is formed, thereby making the nano-scale protrusions on the surface of the PVC material more numerous and more uniform, thereby further improving the hydrophobicity and mechanical strength of the PVC material.
[0014] Optionally, the titanate coupling agent is tetraisopropyl di(dioctylphosphite) titanate.
[0015] By adopting the above technical solution, the combined effect of combining the surface modification effect and the effect of reducing the hydrophobicity of the anti-sticking layer is better, and the obtained PVC material has better hydrophobicity.
[0016] Optionally: the mixed solution also includes methyltrimethoxysilane.
[0017] By adopting the above technical solution, the steric hindrance of tridecafluorooctyl trimethoxysilane is large, the hydrolysis cross-linking reaction is slow, the final cross-linking network is short, the adhesion rate of the fluorine-containing groups on the surface of the inorganic hard particles is low, and the bonding strength between the anti-sticking layer and the inorganic hard particles is low; After adding methyltrimethoxysilane and tridecafluorooctyltrimethoxysilane for compound use, the hydrolysis cross-linking reaction is fast, the cross-linking network is long, the adhesion rate of fluorine-containing groups on the surface of the improved additive is high, and the bonding strength between the anti-sticking layer and the inorganic hard particles is good. The obtained PVC material has better hydrophobic improvement effect and mechanical strength.
[0018] Optionally: the inorganic hard particles are silicon carbide.
[0019] By adopting the above technical solution, the silicon carbide crystal structure is stable and has high strength, and the particles after ball milling are complete and have good retained strength, thereby enhancing the mechanical properties of the PVC material.
[0020] The above second invention objective of the present invention is achieved through the following technical solutions: A method for preparing a super-hydrophobic PVC material comprises the following steps: Weigh PVC resin, TPE titanium dioxide and CR modified additive according to the mass ratio, add them into a mixer and mix them evenly to obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0021] By adopting the above technical solution, the preparation method is convenient and can be produced relying on existing process equipment.
[0022] The above second invention objective of the present invention is achieved through the following technical solutions: A PVC drainage pipe is made from the above-mentioned super-hydrophobic PVC material.
[0023] By adopting the above technical solution, the surface of the PVC drainage pipe of the present application has excellent hydrophobicity and is not easy to accumulate hair.
[0024] In summary, this application has at least the following beneficial effects: 1. The PVC material of the present application can add less fluorine-containing organosiloxane cross-linked solidified material, while maintaining the strength performance of the PVC material up to standard, and hydrophobic modification is performed on the surface of the PVC material to form a large number of hydrophobic nano-convex points, which significantly improves the hydrophobicity of the surface of the PVC material, reduces the infiltration of water on the surface of the PVC material, and makes it easier to wash away hair, thereby reducing the accumulation of hair on the inner wall of the PVC tube made of the PVC material; 2. By covering the surface of the inorganic hard particles with a fluorine-containing organosiloxane cross-linked solidified material, breaking them, then covering them with a fluorine-containing organosiloxane cross-linked solidified material, and then breaking them again, the coverage density of the anti-sticking layer on the modified auxiliary agent particles can be gradually increased or decreased, and a "pole" is formed in the area with the maximum coverage density of the anti-sticking layer. The compatibility between the pole on the anti-sticking layer and the PVC resin is relatively the worst, and the compatibility between the anti-sticking layer and the PVC resin in the area far away from the "pole" is relatively good, so that the modified auxiliary agent is easier to migrate and disperse to the surface of the PVC material, and it is easier to form nano-scale protrusions outward from the "pole", and the resulting PVC material has better hydrophobicity; 3. The mixed solution of the improvement additive is a compound of methyltrimethoxysilane and tridecafluorooctyltrimethoxysilane, which has a fast hydrolysis and cross-linking reaction, a long cross-linking network, a high adhesion rate of fluorinated groups on the surface of the improvement additive, and a good bonding strength between the anti-sticking layer and the inorganic hard particles. The obtained PVC material has a better hydrophobic improvement effect and mechanical strength; 4. The inorganic hard particles are silicon carbide, which has high strength. The particles after ball milling are complete and retain good strength, thus enhancing the mechanical properties of PVC materials. DETAILED DESCRIPTION
[0025] raw material The PVC resin is the SG-5 product of Xinfa Group; TPE is PolyOne brand G7820 N product; The titanium dioxide was Chemours R103 with a particle size of 0.23 μm; CR is chloroprene rubber, a long-life CR244 type 1 product; Silicon carbide is a commercially available product with a purity of 99wt% and a true density of 3.21g / cm 3 , particle size specifications are 1.5±0.5μm, 8±1μm, 350±50nm; Silica is commercially available white carbon black with a true density of 2.42 g / cm 3 , the particle size specification is 1.5±0.5μm.
[0026] Titanate coupling agents include tetraisopropyl di(dioctylphosphite) titanate and isopropyl triisostearate titanate, which were purchased from Nanjing Pinning Coupling Agent Co., Ltd. γ-Aminopropyltriethoxysilane, tridecafluorooctyltrimethoxysilane, methyltrimethoxysilane, ethanol, water, and tetramethylammonium hydroxide are all commercially available industrial grade products.
[0027] Preparation Example 1 A modification auxiliary agent, which has silicon carbide as a core and a surface comprising a continuous anti-adhesive layer and a bonding surface not covered with anti-adhesive. The anti-adhesive layer is formed by curing fluorine-containing organic siloxane.
[0028] The specific preparation method is as follows: 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol, and 16 kg of water were mixed to obtain a mixed solution; Add 4.3 kg of 1.5±0.5 μm silicon carbide particles to the mixed solution, add methyltrimethoxysilane during stirring to adjust the liquid pH to 8.5, heat to 50° C., react for 3 h, filter and dry to obtain modified inorganic hard particles; Add the modified inorganic hard particles into a ball mill and crush them in a dispersion medium until the particle D80 is 350±50 nm to obtain a crushed slurry; The crushed slurry is filtered, dried, and then sieved to obtain particles with a particle size of 300 to 400 nm to obtain a modified auxiliary agent.
[0029] The dispersion medium is a mixture of polyethylene glycol 400, ethanol and water in a mass ratio of 8:60:40, and the mass ratio of the modified inorganic hard particles to the dispersion medium in the ball mill is 1:2.7.
[0030] Preparation Example 2 A modification aid, which differs from Preparation Example 1 in that it uses silicon dioxide as a core, and during preparation, 3.24 kg of 1.5±0.5 μm silicon dioxide particles are used to replace 4.3 kg of 1.5±0.5 μm silicon carbide particles. The actual volume of the 3.24 kg silicon dioxide particles is equal to the actual volume of the 4.3 kg of 1.5±0.5 μm silicon carbide particles.
[0031] Preparation Example 3 A modification auxiliary agent, which is different from Preparation Example 1 in that the mixed liquid is obtained by uniformly mixing 4.2 kg of tridecafluorooctyltrimethoxysilane, 1.6 kg of anhydrous ethanol and 16 kg of water.
[0032] Preparation Example 4 A modification auxiliary agent, which has silicon carbide as a core and a surface comprising a continuous anti-adhesive layer and a bonding surface not covered with anti-adhesive. The anti-adhesive layer is formed by curing fluorine-containing organic siloxane.
[0033] The specific preparation method is as follows: 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol, and 16 kg of water were mixed to obtain a first mixed solution; 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol and 16 kg of water were mixed to obtain a second mixed solution; Add 4.3 kg of 8±1 μm silicon carbide particles to the first mixed liquid, add methyltrimethoxysilane during stirring to adjust the liquid pH to 8.5, heat to 50° C., react for 3 hours, filter and dry to obtain primary modified particles; The first-stage modified particles are added into a ball mill and crushed in a dispersion medium until D80 is 4±0.2 μm to obtain a first-stage slurry; The first-stage slurry is filtered, dried, and sieved to obtain particles with a particle size of 4±0.3 μm to obtain intermediate particles; The intermediate particles are added to the second mixed liquid, the mass ratio of the intermediate particles to the second mixed liquid is 1:5, methyltrimethoxysilane is added during stirring to adjust the liquid pH to 8.5, and then heated to 50° C. for reaction for 3 hours, filtered and dried to obtain secondary modified particles; The secondary modified particles are added into a ball mill and crushed in a dispersion medium until D80 is 350±50 nm to obtain a secondary slurry; The secondary slurry is filtered, dried, and then sieved to obtain particles with a particle size of 350±50 nm to obtain composite improved particles.
[0034] The composite improved particles are used as modification aids.
[0035] The dispersion medium is a mixture of polyethylene glycol 400, ethanol and water in a mass ratio of 8:60:40, and the mass ratio of the modified inorganic hard particles to the dispersion medium in the ball mill is 1:2.7.
[0036] Preparation Example 5 A modification auxiliary agent, which has silicon carbide as a core and a surface comprising a continuous anti-adhesive layer and a bonding surface not covered with anti-adhesive. The anti-adhesive layer is formed by curing fluorine-containing organic siloxane.
[0037] The specific preparation method is as follows: 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol, and 16 kg of water were mixed to obtain a first mixed solution; 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol and 16 kg of water were mixed to obtain a second mixed solution; Add 4.3 kg of 1.5±0.5 μm silicon carbide particles to the first mixed liquid, add methyltrimethoxysilane during stirring to adjust the liquid pH to 8.5, heat to 50° C., react for 3 h, filter and dry to obtain primary modified particles; The primary modified particles are added to the second mixed solution, methyltrimethoxysilane is added during stirring to adjust the pH of the liquid phase to 8.5, and then heated to 50° C. for reaction for 3 hours, filtered and dried to obtain secondary modified particles; The secondary modified particles are added into a ball mill and crushed in a dispersion medium until D80 is 350±50 nm to obtain a secondary slurry; The secondary slurry is filtered, dried, and then sieved to obtain particles with a particle size of 350±50 nm to obtain composite improved particles.
[0038] The composite improved particles are used as modification aids.
[0039] The dispersion medium is a mixture of polyethylene glycol 400, ethanol and water in a mass ratio of 8:60:40, and the mass ratio of the modified inorganic hard particles to the dispersion medium in the ball mill is 1:2.7.
[0040] Preparation Example 6 A modification aid is provided, which is based on Preparation Example 4 and further improved on the composite modified particles obtained in Preparation Example 4.
[0041] The composite modified particles, water and tetraisopropyl di(dioctylphosphite) titanate were mixed in a mass ratio of 10:40:1.2, heated to 32° C., stirred for reaction for 30 minutes, filtered and dried to obtain a modified auxiliary agent.
[0042] Preparation Example 7 A modification aid is provided, which is based on Preparation Example 4 and further improved on the composite modified particles obtained in Preparation Example 4.
[0043] The composite modified particles, water and isopropyl titanate triisostearate were mixed in a mass ratio of 10:40:1.2, heated to 32° C., stirred for reaction for 30 minutes, filtered and dried to obtain a modified auxiliary agent.
[0044] Preparation Example 8 A fluorine-containing organosilicon microsphere, the preparation method of which is as follows: 1.5 kg of tridecafluorooctyltrimethoxysilane, 2.7 kg of methyltrimethoxysilane, 1.6 kg of anhydrous ethanol and 16 kg of water were mixed evenly to obtain a mixed solution, and methyltrimethoxysilane was added to the mixed solution to adjust the liquid pH to 8.5. The mixture was heated to 50°C and reacted for 5 hours. The mixture was filtered and dried, and particles of 350±50 nm were screened to obtain fluorinated silicone microspheres.
[0045] Example 1 A super-hydrophobic PVC material, whose raw materials are PVC resin, TPE, titanium dioxide, CR and a modification auxiliary agent.
[0046] The specific preparation process is as follows: Weigh 100 kg of PVC resin, 2 kg of TPE, 1.8 kg of titanium dioxide, 2.4 kg of CR, and 10 kg of modification aid, add them into a mixer, mix them evenly, and obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0047] During extrusion, the screw extruder can extrude into granules, extrude into pipes, or extrude into sample molds to prepare test samples according to production needs.
[0048] The modified auxiliary agent is prepared in Preparation Example 1.
[0049] Example 2 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 2.
[0050] Example 3 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 3.
[0051] Example 4 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 4.
[0052] Example 5 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 5.
[0053] Example 6 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 6.
[0054] Example 7 A super-hydrophobic PVC material, which differs from Example 1 in that the modification aid is prepared in Preparation Example 7.
[0055] Example 8 A super-hydrophobic PVC material, which differs from Example 6 in that the amounts of raw materials used are different, specifically as follows: 100 kg PVC resin, 1 kg TPE, 1.5 kg titanium dioxide, 3 kg CR, and 5 kg modification aid.
[0056] Example 9 A super-hydrophobic PVC material, which differs from Example 6 in that the amounts of raw materials used are different, specifically as follows: 100 kg PVC resin, 3 kg TPE, 2 kg titanium dioxide, 1 kg CR, and 12 kg modification aid.
[0057] Comparative Example 1 A super-hydrophobic PVC material, whose raw materials are PVC resin, TPE, titanium dioxide and CR.
[0058] The specific preparation process is as follows: Weigh 100 kg of PVC resin, 2 kg of TPE, 1.8 kg of titanium dioxide, and 2.4 kg of CR, add them into a mixer and mix them evenly to obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0059] During extrusion, the screw extruder can extrude into granules, extrude into pipes, or extrude into sample molds to prepare test samples according to production needs.
[0060] Comparative Example 2 A super-hydrophobic PVC material, whose raw materials are PVC resin, TPE, titanium dioxide, CR and 350±50nm silicon carbide powder.
[0061] The specific preparation process is as follows: Weigh 100 kg of PVC resin, 2 kg of TPE, 1.8 kg of titanium dioxide, 2.4 kg of CR, and 10 kg of 350±50 nm silicon carbide powder, add them into a mixer and mix them evenly to obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0062] During extrusion, the screw extruder can extrude into granules, extrude into pipes, or extrude into sample molds to prepare test samples according to production needs.
[0063] Comparative Example 3 A super-hydrophobic PVC material, whose raw materials are PVC resin, TPE, titanium dioxide, CR and fluorine-containing organic silicon particles.
[0064] The fluorine-containing organosilicon particles were prepared in Preparation Example 8.
[0065] The specific preparation process is as follows: Weigh 100 kg of PVC resin, 2 kg of TPE, 1.8 kg of titanium dioxide, 2.4 kg of CR, and 10 kg of fluorinated silicone particles, add them into a mixer, mix them evenly, and obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0066] During extrusion, the screw extruder can extrude into granules, extrude into pipes, or extrude into sample molds to prepare test samples according to production needs.
[0067] Comparative Example 4 A super-hydrophobic PVC material, whose raw materials are PVC resin, TPE, titanium dioxide, CR, fluorine-containing organic silicon particles and EAA.
[0068] The fluorine-containing organosilicon particles were prepared in Preparation Example 8.
[0069] The specific preparation process is as follows: Weigh 100 kg of PVC resin, 2 kg of TPE, 1.8 kg of titanium dioxide, 2.4 kg of CR, 10 kg of fluorinated silicone particles, and 4.2 kg of EAA, add them into a mixer, mix them evenly, and obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
[0070] During extrusion, the screw extruder can extrude into granules, extrude into pipes, or extrude into sample molds to prepare test samples according to production needs.
[0071] The PVC materials of Examples 1 to 9 and Comparative Examples 1 to 4 were tested, including hydrophobicity-water contact angle test and material impact strength test.
[0072] Hydrophobicity-water contact angle test: The PVC material was made into a thin plate, and the water contact angle test was carried out according to GB / T 30693-2014.
[0073] Material impact strength test: The super-hydrophobic PVC material of the present application can be independently prepared as a pipe, or can be prepared as the inner layer of a multi-layer composite pipe. Therefore, the super-hydrophobic PVC material of the present application is not tested by pipe specimens, but is tested according to the A-type notched specimen in GB / T 1843-2008.
[0074] The test results are shown in Table 1 below.
[0075] Table 1. Test results of Examples 1 to 9 and Comparative Examples 1 to 4 It can be seen from Table 1 above that compared with Comparative Example 1, Example 1 adds a modified auxiliary agent to the raw materials, and the water contact angle of Example 1 is significantly greater than that of Comparative Example 1, and the impact strength of Example 1 is greater than that of Comparative Example 1. Therefore, the addition of a modified auxiliary agent to the PVC material in the present application can effectively improve the surface hydrophobicity of the PVC material, reduce hair accumulation, and at the same time ensure that the strength performance of the PVC material does not decrease.
[0076] Combined with Comparative Example 2, compared with Comparative Example 1, silicon carbide powder with the same particle size as the improving auxiliary agent is added to the raw material. Although the impact strength of Comparative Example 2 is improved compared with Comparative Example 1, the water contact angle of Comparative Example 2 is slightly improved compared with Comparative Example 1, which is far less than that of Example 1. Therefore, it can be seen that a single silicon carbide particle cannot achieve a significant improvement in the hydrophobicity of the surface of the PVC material.
[0077] Combined with Comparative Example 3, in Comparative Example 3, fluorinated organosilicon particles were added to PVC for modification. The water contact angle of Comparative Example 3 was increased compared with that of Comparative Example 1, and the increase was greater than that of Comparative Example 2, but still less than that of the embodiment, and the impact strength of Comparative Example 3 was significantly decreased compared with that of Comparative Example 1. This is because the fluorinated organosilicon particles have poor compatibility in PVC, are not evenly distributed on the surface of the PVC material, and agglomeration of particles occurs in the PVC material, so the hydrophobic modification effect is poor and the material strength is reduced.
[0078] Combined with Comparative Example 4, it can be seen that Comparative Example 4 adds EAA on the basis of Comparative Example 3 to improve the compatibility of fluorinated silicone particles in PVC. Corresponding to the test results, the water contact angle of Comparative Example 4 is greater than that of Comparative Example 3, and the impact strength of Comparative Example 4 is greater than that of Comparative Example 3. However, the water contact angle of Comparative Example 4 is still not as good as that of Example 1, and the impact strength of Comparative Example 4 is still less than that of Comparative Example 1. The addition of the compatibilizer cannot completely compensate for the reduced strength of the PVC material caused by the fluorinated silicone particles.
[0079] In summary, with inorganic hard particles as the core, the surface has both a continuous anti-sticking layer and an uncovered anti-sticking bonding surface. The compatibility of the bonding surface with the PVC resin is better than that of the anti-sticking layer with the PVC resin. Due to the existence of the bonding surface, the modified additive can be evenly dispersed into the PVC resin under the shear force when the PVC resin is melted, thus avoiding the agglomeration of the modified additive. Then, due to the existence of the anti-adhesive layer, the dispersion of the modifying agent in the PVC resin is not completely homogeneous. The distribution density of the modifying agent on the surface of the PVC material is greater than that inside the PVC material. In addition, due to the compatibility of the anti-adhesive layer and the tension of the PVC resin when it is melted, the modifying agent also forms nano-scale convex points when it is dispersed on the surface of the PVC material. Thus, while maintaining the strength performance of the PVC material up to standard, the hydrophobicity of the PVC material surface is modified and a large number of hydrophobic nano-protrusions are formed, thereby improving the hydrophobicity of the PVC material surface, making it easier to wash away hair, and reducing hair accumulation on the inner wall of the PVC material.
[0080] By comparing Example 1 and Example 2, it can be seen that the water contact angles of Example 1 and Example 2 are similar, while the impact strength of Example 1 is greater than the impact strength of Example 2. Therefore, when silicon carbide is selected as the core of the improved auxiliary agent, the structure of silicon carbide is stable, the particles after ball milling are complete and retain good strength, and the strength enhancement effect on the PVC material is better.
[0081] By comparing Example 1 and Example 3, it can be seen that the anti-sticking layer of the modified agent used in Example 1 is obtained by hydrolysis and cross-linking of tridecafluorooctyltrimethoxysilane and methyltrimethoxysilane, and the anti-sticking layer of the modified agent used in Example 3 is obtained by hydrolysis and cross-linking of tridecafluorooctyltrimethoxysilane. The water contact angle of Example 1 is greater than that of Example 3, and the impact strength of Example 1 is greater than that of Example 3. The reason is that tridecafluorooctyltrimethoxysilane has large steric hindrance, and the hydrolysis and cross-linking reaction of a single tridecafluorooctyltrimethoxysilane is slow, resulting in a short cross-linking network, a low adhesion rate of fluorinated groups on the surface of inorganic hard particles, and a low bonding strength between the anti-sticking layer and the inorganic hard particles; while tridecafluorooctyltrimethoxysilane and methyltrimethoxysilane are hydrolyzed and cross-linked together, and methyltrimethoxysilane can be used as a hydrolysis product for connecting and cross-linking two tridecafluorooctyltrimethoxysilanes after hydrolysis, so that the cross-linking network is long, the adhesion rate of fluorinated groups on the surface of the modified auxiliary agent is high, and the bonding strength between the anti-sticking layer and the inorganic hard particles is good. Therefore, the hydrophobicity and impact strength of Example 1 are better than those of Example 3. In the mixed solution used for the modified auxiliary agent in this application, a compound of tridecafluorooctyltrimethoxysilane and methyltrimethoxysilane is preferred.
[0082] Comparing Example 1 and Example 4, the impact strength of Example 4 is equal to that of Example 1, while the water contact angle of Example 4 is increased compared with that of Example 1. This is because the preparation method of the improving agent of Example 4 is different from that of the improving agent of Example 1, and the adhesion of the anti-sticking layer on the obtained improving agent is different.
[0083] The improved auxiliary agent of Example 4 is formed by covering the surface of inorganic hard particles with a fluorine-containing organic siloxane cross-linked solidified material, crushing, then covering with a fluorine-containing organic siloxane cross-linked solidified material, and then crushing again, so that the coverage density of the anti-sticking layer on the modified auxiliary agent particles gradually increases or decreases, and then a "pole" is formed in the area with the maximum coverage density of the anti-sticking layer. The compatibility between the pole on the anti-sticking layer and the PVC resin is relatively the worst, and the compatibility between the anti-sticking layer and the PVC resin away from the "pole" area is relatively good. The modified auxiliary agent is easier to migrate and disperse to the surface of the PVC material, and it is easier to form nano-scale protrusions outward from the "pole". Therefore, the water contact angle of Example 4 is larger than that of Example 1, and the hydrophobicity of the PVC material of Example 4 is further improved.
[0084] Combined with Example 5, it can be further seen that the water contact angle of Example 5 is increased compared with that of Example 1, but the increase is significantly less than that of Example 4, and the impact strength of Example 5 is decreased compared with that of Example 1. The reason is that the thickness of the anti-sticking layer on the modified auxiliary agent particles in Example 5 increases uniformly and does not form a "pole", so the nano-scale protrusions formed after the modified auxiliary agent migrates to the surface of the PVC material are less than those in Example 4, and since the anti-sticking layer thickens uniformly, the compatibility also causes a slight decrease in the impact strength of the PVC material.
[0085] Comparing Example 4 with Examples 6-7, it can be seen that, compared with Example 4, Examples 6-7 also mentioned the modification of the modification aid with a titanate coupling agent. The compatibility of the titanate coupling agent with the cross-linked cured product of fluorinated organic siloxane is relatively weak. The titanate coupling agent can effectively modify the surface formed by the new crushing of the composite modified particles, enhance the compatibility of the binding surface with the PVC resin, and form another "pole" with good compatibility with the PVC resin, so that the hydrophobicity and mechanical strength of the PVC materials of Examples 6-7 are improved, and the water contact angle and impact strength of Examples 6-7 are greater than those of Example 1. In addition, the water contact angle of Example 6 is greater than that of Example 7, because tetraisopropyl di(dioctylphosphite) titanate is a hexacoordinated titanate, which is less likely to react with a silicon-oxygen bond than a tetracoordinated titanate, so it has less impact on the anti-adhesive layer, so the PVC material has better hydrophobicity.
[0086] By comparing Comparative Example 1 and Examples 8 to 9, it can be seen that the water contact angle and impact strength of Examples 8 to 9 are significantly greater than those of Comparative Example 1. Therefore, when the mass ratio of PVC resin, TPE, titanium dioxide, CR, and modifying additive in the PVC material of the present application is controlled to be 100:(1 to 3):(1.5 to 2):(1 to 3):(5 to 12), the hydrophobicity of the PVC material is significantly improved while maintaining the strength performance of the PVC material up to standard, so that the hair accumulation on the inner wall of the PVC pipe made of the PVC material is easier to be washed away, thereby reducing the hair accumulation on the inner wall of the PVC pipe.
[0087] Example 10 A PVC drainage pipe is made of PVC material. The PVC material is one of Examples 1 to 9. The surface of the PVC drainage pipe has excellent hydrophobicity and is not easy to accumulate hair.
[0088] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.
Claims
1. A super-hydrophobic PVC material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of PVC resin, TPE 1~3 parts, 1.5~2 parts of titanium dioxide, CR 1~3 copies, Modification additive 5~12 parts, The particle size of the modified auxiliary agent is 300-400 nm. The modification auxiliary agent has inorganic hard particles as the core, and comprises a continuous anti-sticking layer and a bonding surface not covered with anti-sticking. The anti-sticking layer is formed by curing fluorine-containing organic siloxane.
2. A super-hydrophobic PVC material according to claim 1, characterized in that, The preparation method of the modified auxiliary agent is as follows: Inorganic hard particles of 0.6-2 μm are added to the mixed solution for reaction, and after the reaction, the modified inorganic hard particles are obtained by filtering and drying. The modified inorganic hard particles are crushed by ball milling to obtain a slurry, and the slurry is filtered, dried and sieved to obtain a modified auxiliary agent; The mixed liquid includes water and tridecafluorooctyltrimethoxysilane.
3. A super hydrophobic PVC material according to claim 1, characterized in that, The preparation method of the modified auxiliary agent is as follows: Add 7-9 μm inorganic hard particles into the mixed solution for reaction, filter and dry after the reaction to obtain primary modified particles. The first modified particles are ball-milled to obtain a first slurry, and the first slurry is filtered, dried and sieved to obtain intermediate particles; The intermediate particles are added to another mixed solution for reaction, and after the reaction, filtered and dried to obtain secondary modified particles; The secondary modified particles are crushed by ball milling to obtain secondary slurry, the secondary slurry is filtered, the filtered material is dried and sieved to obtain composite modified particles; The mixed liquid includes water and tridecafluorooctyltrimethoxysilane.
4. A super hydrophobic PVC material according to claim 3, characterized in that: The composite modified particles are also modified by soaking in a titanate coupling agent solution.
5. A super-hydrophobic PVC material according to claim 4, characterized in that: The titanate coupling agent is tetraisopropyl di(dioctylphosphite) titanate.
6. A super-hydrophobic PVC material according to claim 2, characterized in that: The mixed solution also includes methyltrimethoxysilane.
7. A super-hydrophobic PVC material according to claim 1, characterized in that: The inorganic hard particles are silicon carbide.
8. A method for preparing a super-hydrophobic PVC material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh PVC resin, TPE titanium dioxide and CR modified additive according to the mass ratio, add them into a mixer and mix them evenly to obtain a mixed raw material; The mixed raw materials are fed into a screw extruder for melt extrusion.
9. A PVC drainage pipe, characterized in that: It is made from the super-hydrophobic PVC material described in any one of claims 1 to 7.
Citation Information
Cited By
Super-hydrophobic self-cleaning PVC-U condensate pipe for air conditioner and preparation method of super-hydrophobic self-cleaning PVC-U condensate pipe
CN119823511A